Simultaneous Estimation of Atorvastatin and Ezetimibe in Combined Formulation by RP-HPLC - Ganesh, Mani; Hemalatha, Pushparaj; Sakthimanigandan, Kavimani; Mei Mei, Peng; Gil Lee, Seung (Asian Journal of Chemistry, 2011)
A simple, selective, robust and sensitive reversed phase high performance liquid chromatography method has been developed and validated for the simultaneous estimation of atorvastatin and ezetimibe in bulk drug and pharmaceutical formulations. The separation was achieved on a phenomenex Gemini C-18 (250 × 4.6 mm, packed with 5 μ) column by using an isocratic mobile phase mixture composed of acetonitrile: ammonium acetate buffer pH 3.0 (50:50, v/v) with 1.2 mL min-1 as flow rate and the eluents were monitored at 247 nm. The retention times for atorvastatin, ezetimibe were 3.0, 5.2 min respectively, the linearity for both analytes was found to be 80-120 % with reference to labeled claim (10 mg of each components) and with r = 0.9989 and 0.9979 for atorvastatin and ezetimibe respectively. The method was validated for its system suitability, ruggedness, accuracy, precision and stability. The proposed method was successfully employed for the simultaneous quantification of atorvastatin and ezetimibe in their pharmaceutical formulation.